Johor MB proposed cooperation with UMP - UMP, PNC
Universiti Malaysia Pahang top management team led by Vice- Chancellor, Professor Dato’ Dr Daing Nasir Ibrahim paid a courtesy call to Johor Menteri Besar, Yang Amat Berhormat Dato’ Seri Mohd Khalid Nordin on August 29, 2013.